The Effect of Mergers and Acquisitions Strategies on Financial Performance of Commercial Banks in Kenya - Justin Gachigo; Herick Ondigo; Josiah Aduda; Zipporah Onsomu (European Scientific Journal, ESJ, 2022)
The operating environment for commercial banks in Kenya has become very dynamic and highly competitive. The witnessed cases of bank failure and poor financial performance have made commercial banks develop strategies to improve their financial performance, remain competitive, and meet the regulator's compliance requirements. Mergers and Acquisitions Strategies are on the rise as a strategy aimed to alleviate the ailing sector. In light of this, the purpose of this study was to examine the impact on financial performance of commercial banks in Kenya as a result of mergers and acquisitions Strategies. Operating efficiency and market share impact on the financial performance of commercial banks in Kenya formed the specific objectives. The study objectives were supported by synergies theory, resource-based view theory and agency theory. The study adopted a correlational descriptive research design, including cross-sectional data analysis.  By the year 2017, 30 commercial banks in Kenya had considered mergers and acquisitions strategies were considered as the population of this study. An average of three-year ratios was computed in both pre-merger and post -acquisition periods inorder to assess the impact financial performance. The years of the deal were excluded. The mean difference between the pre-Mergers and Acquisitions Strategies and post-Mergers and Acquisitions Strategies ratios was tested using the T-test.The findings were that Mergers and Acquisitions Strategies have a statically positive significant relationship with the dependent variable. Recommends from the study are that, the policymakers create policies that facilitate and encourage commercial banks to employ mergers and acquisition strategies to achieve better financial performance.